An Explicit Hermite-Taylor Method for the Schrödinger Equation. (27th March 2017) - Appelö, Daniel; Kreiss, Gunilla; Wang, Siyang
Abstract: An explicit spectrally accurate order-adaptive Hermite-Taylor method for the Schrödinger equation is developed. Numerical experiments illustrating the properties of the method are presented. The method, which is able to use very coarse grids while still retaining high accuracy, compares favorably to an existing exponential integrator – high order summation-by-parts finite difference method.